A task-centric model for archival metadata schema mapping based on the records lifecycle. (1st January 2012) - Baek, Jaeeun; Sugimoto, Shigeo
Metadata is well recognised as one of the foundational components required in archiving and preservation of digital resources. It is crucial to select and/or combine metadata standards in accordance with requirements in an application domain and in the records lifecycle. Based on our previous research in which we have clarified the features of major standard metadata element sets from a viewpoint of the records lifecycle, this paper proposes a model to help create mappings among the metadata element sets. In this study, we first propose a Task Model to clarify tasks in the records lifecycle and to categorise metadata elements using tasks. Then, this paper proposes to use 5W1H (Who, What, Why, When, Where and How) categories to classify descriptive elements of metadata standards in order to help mapping the elements among metadata standards. In this study, we applied the Task Model and 5W1H categorisation to a set of element sets taken from a number of metadata standards, e.g., AGRkMS, EAD, OAIS, and PREMIS, and created a mapping table among the standards.